Pendidikan Islam Populer: Sebuah Renungan Atas Nasib Pendidikan Madrasah di Tengah Pendidikan Nasional - M. Misbah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: In the course of the history of Islamic education,Islamic schools as institutions of Islamic education was not as expected. One side, in terms of religion, alumni are not able to compete with graduates of boarding schools and on the other hand, in terms of general science, can not compete with public schools. So too, madrasas in education and learning are not in line with communitlr interests, and can not solve the problems faced by society. There has been a "dehumanization" in the practice of education in madrasas. Therefore, to liberate the madrasa education from the process of "dehumanization", as well as for education in accordance with the interests of society, the madrasa education should be society-based (popular) to instilt a spirit critical of social phenomena. Therefore, the critical educational needs in the learning process, cooperation between the madrasas with the community and always do the renewal of the retigious doctrines which have been shallowed. Keywords: Modrasah, Islamic Popular Education, Critical Education.